Complications after partial nephrectomy: robotics overcomes open surgery and laparoscopy: the PMSI French national database - Antoine Bic; Charles Mazeaud; Julia Salleron; Aurélie Bannay; Beverley Balkau; Clément Larose; Jacques Hubert; Pascal Eschwège (BMC Urology, 2023)
Abstract Purpose To evaluate three partial nephrectomies (PN) procedures: open (OPN), standard laparoscopy (LPN), and robot-assisted laparoscopy (RAPN), for the risk of initial complications and rehospitalization for two years after the surgery. Materials and methods From the French national hospital database (PMSI-MCO), every hospitalization in French hospitals for renal tumor PN in 2016–2017 were extracted. Complications were documented from the initial hospitalization and any rehospitalization over two years. Chi-square and ANOVA tests compared the frequency of complications and length of initial hospitalization between the three surgical procedures. Relative risks (RR) and 95% confidence intervals were computed. Results The 9119 initial hospitalizations included 4035 OPN, 1709 LPN, and 1900 RAPN; 1475 were excluded as the laparoscopic procedure performed was not determined. The average length of hospitalization was 8.1, 6.2, and 4.5 days for OPN, LPN, and RAPN, respectively. Compared to OPN, there were fewer complications at the time of initial hospitalization for the mini-invasive procedures: 29% for OPN vs. 20% for LPN (0.70 [0.63;0.78]) and 12% for RAPN (RR=0.43, 95%CI [0.38;0.49]). For RAPN compared to LPN, there were fewer haemorrhages (RR=0.55 [0.43;0.72]), anemia (0.69 {0.48;0.98]), and sepsis (0.51 [0.36;0.71]); during follow up, there were fewer urinary tract infections (0.64 [0.45;0.91]) but more infectious lung diseases (1.69 [1.03;2.76]). Over the two-year postoperative period, RAPN was associated with fewer acute renal failures (RR=0.73 [0.55;0.98]), renal abscesses (0.41 [0.23;0.74]), parietal complications (0.69 [0.52;0.92]) and urinary tract infections (0.54 [0.40;0.73]) than for OPN. Conclusions Conservative renal surgery is associated with postoperative morbidity related to the surgical procedure fashion. Mini-invasive procedures, especially robot-assisted surgery, had fewer complications and shorter hospital lengths of stay